Evaluation of Antioxidant Activity of Methanolic Extracts and some Fractions of Salvia verticillata L. Using Three Different Methods - E Souri; H Farsam; S Ardestani; M Zolfagharifar (Institue of Medicinal Plants, ACECR, 2007)
Background: Bradykinin has effects on histaminic response,vessels seepage,cellular reproduction,causing fever, pain and coughs caused by ACE controllers (3,4,6). Noscapin has controlled Bradykinins contractional effects on guinea pigs trachea and rats vazodofran (5,6). noscapin stops the secondary effects of eskimi in brains edema, with antagonizing the responses caused by Bradykinin (3,4,8). Objective: considering that opium's alkaloids act as agonist of peptide systems like ankephalins and RAS, its interesting to know the effects of this alkaloids and among them Noscapine on B3 Bradykinin receptors on smooth muscle guinea pig trachea? Method: All variables are reported as mean and standard deviation.We have used pair test and the informations were processed by Excel, Statistical analysis with ANOVA (LSD) SPSS 9. Results: we took diagrams in to consideration and indicated that the contract ional effect of Bradykinin decreased dependent on density, in presence of three different amount of noscapines concentration. In this study we could demonstrate that noscapine interact with Bradykenin as a non competitive antagonist.